O vício capital da inveja na visão de Ramon Llull. - DOS SANTOS, ARMANDO ALEXANDRE (Scripta, 2020)
Exposition of Ramon Llull's thought about the capital vice of envy, inserted in the culture and spirituality of the Middle Ages, highlighting its conformity with the spiritual and theological doctrine on the subject, and at the same time his extreme originality in the application practice of that doctrine.